2017
DOI: 10.1093/ageing/afx166
|View full text |Cite
|
Sign up to set email alerts
|

What is Comprehensive Geriatric Assessment (CGA)? An umbrella review

Abstract: we confirm a widely used definition of CGA. Key outcomes are death, disability and institutionalisation. The main beneficiaries in hospital are older people with acute illness. The presence of frailty has not been widely examined as a determinant of CGA outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
264
1
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 380 publications
(312 citation statements)
references
References 20 publications
4
264
1
16
Order By: Relevance
“…Among the risk factors for functional decline, geriatric syndromes are least familiar to the dialysis provider and more likely to be under recognized. Developed as a tool for identification of older patients at risk for nursing home placement, comprehensive geriatric assessment (CGA) is the gold standard for identifying functional decline and other geriatric syndromes that can contribute to functional decline . The standard CGA is characterized by a multidisciplinary team (eg, a geriatrician, nurse, and social worker) that conducts a comprehensive multidimensional evaluation .…”
Section: Identifying Dialysis Patients At Risk Of Functional Declinementioning
confidence: 99%
See 1 more Smart Citation
“…Among the risk factors for functional decline, geriatric syndromes are least familiar to the dialysis provider and more likely to be under recognized. Developed as a tool for identification of older patients at risk for nursing home placement, comprehensive geriatric assessment (CGA) is the gold standard for identifying functional decline and other geriatric syndromes that can contribute to functional decline . The standard CGA is characterized by a multidisciplinary team (eg, a geriatrician, nurse, and social worker) that conducts a comprehensive multidimensional evaluation .…”
Section: Identifying Dialysis Patients At Risk Of Functional Declinementioning
confidence: 99%
“…16 and other geriatric syndromes that can contribute to functional decline. 27 The standard CGA is characterized by a multidisciplinary team (eg, a geriatrician, nurse, and social worker) that conducts a comprehensive multidimensional evaluation. 8,28 The essential dimensions include functional status, cognition, comorbidities, mood, falls, polypharmacy, nutrition, social support, and financial well-being.…”
Section: Comorbidity Disability and Low Physical Activitymentioning
confidence: 99%
“…Currently, the comprehensive geriatric assessment (CGA) is considered as a gold standard to diagnose frailty, which is associated with poor outcomes and higher risks of treatment; therefore, it assesses the biological age, rather than the chronological age per se to identify for treatment (un)suitable patients . A CGA is a multidimensional and interdisciplinary assessment through evaluating physical, psychological, functional, and social capabilities and limitations of the onco‐geriatric patient . Although CGA is the most valid and reliable method, it is very time intensive.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 A CGA is a multidimensional and interdisciplinary assessment through evaluating physical, psychological, functional, and social capabilities and limitations of the onco-geriatric patient. 10 Although CGA is the most valid and reliable method, it is very time intensive. Alternatively, frailty questionnaires are used to identify patients who should undergo a full CGA, 11 which are also time intensive even though it is a shorter procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that frail and disabled elderly patients with substantial multimorbidity are likely to benefit from hospital care provided in a more holistic approach 93 . The CGA is now the accepted "gold standard" in caring for frail elderly patients in hospitals 155 . However, in the literature, there are discussions about who a CGA will benefit most 102,155,156 .…”
Section: Aspects Of Importance Within Cgamentioning
confidence: 99%